ChemInform Abstract: Coupling of Single, Double, and Triple‐Decker Metal‐Phthalocyanine Complexes to Ferromagnetic and Antiferromagnetic Substrates. Issue 51 (23rd December 2014) - Lodi Rizzini, Alberto; Krull, Cornelius; Mugarza, Aitor; Balashov, Timofey; Nistor, Corneliu; Piquerel, Raoul; Klyatskaya, Svetlana; Ruben, Mario; Sheverdyaeva, Polina M.; Moras, Paolo; et al., et al.
Abstract Review: 111 refs.